Lived Experiences of Adolescents Undergoing Rehabilitation After Sports-Related Concussions: A Phenomenological Approach - Saadati, Seyed Milad; Khadem Fini, Armin (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the lived experiences of adolescents undergoing rehabilitation after sports-related concussions (SRCs). Methods and Materials: A qualitative research design grounded in a phenomenological approach was employed to capture the essence of participants’ subjective experiences. Twenty adolescents aged 13–18 years, all from Minnesota and with a medically diagnosed SRC within the past 12 months, were recruited through purposive sampling from rehabilitation clinics, sports medicine centers, and school athletic departments. Data were collected through semi-structured, in-depth interviews conducted in private, comfortable settings and lasting between 45 and 75 minutes. Interviews explored participants’ symptoms, coping strategies, academic reintegration, and social support networks. Recruitment continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo 14 software. Findings: Four major themes emerged: (1) Physical and Cognitive Recovery Challenges, encompassing persistent symptoms, fluctuating recovery patterns, and adaptation to modified routines; (2) Emotional and Psychological Adjustment, including emotional distress, identity disruption, coping mechanisms, and social withdrawal; (3) Academic and School Reintegration, highlighting classroom challenges, the role of accommodations, and teacher and peer support; and (4) Social and Familial Support Systems, involving family engagement, team and coach encouragement, community resources, and experiences of misunderstanding. Conclusion: Recovery from SRCs in adolescence is a multifaceted process shaped by interrelated physical, cognitive, psychological, academic, and social factors. Effective rehabilitation requires multidisciplinary, individualized approaches that address both clinical recovery and the lived realities of young athletes, incorporating medical, educational, and psychosocial support to optimize outcomes.